Connecting the local narratives: public administration as a hermeneutic science - Balfour Danny L.; Mesaros William
Does hermeneutics provide a useful framework for the study and practice of public administration? Danny L. Balfour and William Mesaros argue that a shift toward the hermeneutic perspective can move public administration towards the cutting edge of social research and practice while promoting the values of mutuality, understanding, and improved communication. Hermeneutics can help field move away from methodological debates and toward more practical, cooperative research and an enhanced focus on the substantive issues that define and energize public policy and administration.
Keywords: Public Administration